Pendampingan terkait Konsep diri, Kepemimpinan & Kewirausahaan bagi Pelajar SMA/SMK/MA Penerima Beasiswa BAZNAS Daerah Istimewa Yogyakarta Tahun Anggaran 2019 - Andriyastuti Suratman; Majang Palupi (Universitas Katolik Soegijapranata, 2019)
This activity is initiated by a community service team with BAZNAS Special Region of Yogyakarta (Daerah Istimewa Yogyakarta) as a partner. This activity was funded by Directorate of Research and Community Service (Direktorat Penelitian dan Pengabdian Masyarakat) of Universitas Islam Indonesia. This team did synergy with BAZNAS DIY that has scholarships program for high school - SMA/SMK/Madrasah Aliyah students totaling 105 participants in the entire Yogyakarta Province. Mentoring was delivered in three stages or meetings; about Islamic self-concept and SWOT analysis with classical method, leadership and teamwork with outbond method and entrepreneurship with classical and student center learning by forum group discussion. This activity was also preceded by a forum discussion with BAZNAS DIY leaders and ended with a report.